The long loneliness : An autobiography - Day, Dorothy (New York HarperCollins, 1981)
A compelling autobiographical testament to the spiritual pilgrimage of a woman who, in her own words, dedicated herself "to bring[ing] about the kind of society where it is easier to be good."
D., 8/2000
Keywords: Day, Dorothy -- Biography; Converts, Catholic -- Biography. -- United States